Evaluation of Colorimetric BCA-Based Quantification of Hydrazide Groups on Magnetic Particles - Zuzana Svobodova; Barbora Jankovicova; Zdenek Plichta; Daniel Horak; Zuzana Bilkova (Journal of Spectroscopy)
Magnetic micro- and nanoparticles (MPs) are considered to provide excellent solid support for many immunoanalytical and bioaffinity applications, particularly when they contain hydrazide groups available for site-specific immobilization of various glycoproteins, such as immunoglobulin G and enzymes. To prepare a highly active bioaffinity carrier with sufficient binding capacity, knowledge as to the type and concentration of functional groups used for ligand binding is crucial. Described here is a simple, nontoxic method for rapid estimation of hydrazide functional groups bound to MPs using bicinchoninic acid (BCA). BCA kits are routinely used for colorimetric detection and quantification of total protein in liquid samples. In this study, the BCA reagent was applied for quantification of hydrazide groups on MPs. The approach was carried out using an adipic acid dihydrazide (ADH) solution and subsequently using various hydrazide-containing magnetic and nonmagnetic carriers differing in the density of hydrazide groups. The BCA test’s results obtained on the MPs were compared with those from conventional amino and hydrazide group quantification by the 2,4,6-trinitrobenzenesulfonic acid (TNBS) test.